Hodnocení finanční situace společnosti a návrhy na její zlepšení - Zatloukalová, Štěpánka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Tato bakalářská práce se věnuje zhodnocením finanční situace vybraného podniku v letech 2015 až 2019. Hodnocení je založeno na základě metod a ukazatelů finanční analýzy, které jsou podrobně popsány v teoretické části. V praktické části jsou teoretické poznatky aplikovány na konkrétní společnost. Na základě zjištěných výsledků jsou v poslední části práce navržena doporučení pro zlepšení finanční situace.

The bachelor’s thesis deals with the evaluation of the selected company during the years 2015 to 2019. Evaluation is based on methods and indicators of the financial analysis, which are particularly described in the theoretical part. The theoretical information is implicated for the particular company in the practical part of the thesis. Finally, based on the findings, there are suggested recommendations for improvement of the financial situation.
Evaluation of the Financial Situation in the Company and Proposals to its improvement
Keywords: Finanční analýza; SLEPTE analýza; Porterova analýza; soustavy ukazatelů; absolutní ukazatele; rozdílové ukazatele; poměrové ukazatele; Financial analysis; SLEPTE analysis; Porter’s analysis; systems of indicators; absolute indicators; difference indicators; ration indicators